Man on the Spot: John Daly, Indian Agent in Parry Sound, 1922-1939 - Brownlie, Robin (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 1994)
AbstractIn this article, the local application of Indian policy is examined though an analysis of the career of an Ontario Indian agent, John M. Daly, who served in the Parry Sound Agency from 1922 to 1939. While policy was decided in Ottawa, which closely monitored field officials, the agents were responsible for its practial implementation and for dealing with the contradictions and ambiguities which could arise in concrete situations. The Indian Department's reliance on information provided by the "man on the spot" meant that his recommendations carried a great deal of weight in decision-making. An in-depth analysis of the agent's day-to-day activities thus provides insights into the actual realities faced by Native people in their interaction with government. Daly's methods conformed well to the style of administration encouraged by the Department. A confirmed paternalist, he offered some protection to vulnerable individuals while opposing those who strove to assert self-determinaiton. He was always very concerned to maintain the Department's authority, on which his own was dependent — in particular, this involved keeping aboriginal people and band councils "in their place". By the 1920s the failure of the federal policy of separation, civilisation and assimilation was readily apparent — aboriginal people remained a distinct, unassimilated population, still largely segregated on the reserves which were intended to be absorbed into the surrounding communities. The formerly stagnant or shrinking Native population was beginning to increase, while reserves remained fixed in size and their resources were already substantially depleted. This, combined with the marginalization of aboriginal people within the mainstream labour market, meant poverty and hardship for many Natives. Since federal policy was never adjusted to cope with the new realities, the agents found themselves approaching the problem of Native poverty on an ad hoc basis. Daly's negotiation of these difficult circumstances is analysed in the following paper.